(untitled) (CAHIERS MAGELLANES-NS, 2024)
Cross-functional integration between marketing and human resources (HR) has emerged as a strategic approach to fostering employee engagement, particularly in dynamic sectors like fintech. This review paper explores how collaboration between marketing and HR departments can enhance employee engagement and create a cohesive organizational culture that aligns with both customer-centric and employee-driven goals. In the fintech industry, which thrives on innovation, adaptability, and rapid technological advancements, maintaining a motivated and engaged workforce is critical for sustained success. The paper examines the theoretical foundations of cross-functional collaboration and its practical implications for improving employee satisfaction, retention, and overall performance in fintech companies. It highlights key synergies between marketing and HR, such as internal branding, employee value proposition (EVP), and leveraging marketing’s expertise in communication to strengthen HR’s employee engagement strategies. Additionally, the paper explores case studies from leading fintech companies to demonstrate how integrated efforts between these two functions have driven employee motivation, innovation, and alignment with organizational objectives. By analyzing existing literature and organizational practices, this review identifies best practices for implementing cross-functional collaboration between marketing and HR. It also addresses potential challenges, such as misaligned objectives or communication barriers, and offers recommendations for overcoming these issues. The findings suggest that fintech firms can significantly benefit from a unified approach that leverages the strengths of both marketing and HR to build a strong, engaged workforce, ultimately contributing to enhanced business outcomes in a highly competitive market.